2020
DOI: 10.1111/jch.14074
|View full text |Cite
|
Sign up to set email alerts
|

Insights on home blood pressure monitoring in Asia: Expert perspectives from 10 countries/regions

Abstract: Hypertension is one of the most powerful modifiable risk factors for cardiovascular disease. It is usually asymptomatic and therefore essential to measure blood pressure regularly for the detection of hypertension. Home blood pressure monitoring (HBPM) is recognized as a valuable tool to monitor blood pressure and facilitate effective diagnosis of hypertension. It is useful to identify the masked or white‐coat hypertension. There is also increasing evidence that supports the role of HBPM in guiding antihyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 36 publications
(119 reference statements)
0
16
0
Order By: Relevance
“…In fact, the two out-of-office blood pressure measuring techniques are complementary in almost all aspects of hypertension management. ABPM substantially improves the diagnostic accuracy of hypertension by providing a 24-hour blood pressure profile, whereas HBPM is of particular importance in blood pressure control by improving treatment adherence [62,63] . However, the new technology of wearable devices might combine these two out-of-office techniques and provide accurate and comprehensive blood pressure evaluations in the future [64] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the two out-of-office blood pressure measuring techniques are complementary in almost all aspects of hypertension management. ABPM substantially improves the diagnostic accuracy of hypertension by providing a 24-hour blood pressure profile, whereas HBPM is of particular importance in blood pressure control by improving treatment adherence [62,63] . However, the new technology of wearable devices might combine these two out-of-office techniques and provide accurate and comprehensive blood pressure evaluations in the future [64] …”
Section: Discussionmentioning
confidence: 99%
“…HBPM is increasingly available and usable in the management of hypertension. [62] In fact, the two out-of-office blood pressure measuring techniques are complementary in almost all aspects of hypertension management. ABPM substantially improves the diagnostic accuracy of hypertension by providing a 24-hour blood pressure profile, whereas HBPM is of particular importance in blood pressure control by improving treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also important to note that current use and awareness of HBPM varies between regions and countries, and between specialists and general practitioners. 97 There are also a number of challenges that need to be overcome to facilitate the widespread implementation of an HBPM-based approach to hypertension management. These include a lack of awareness about the clinical value of HBPM, insufficient knowledge about HBPM best practices, and a lack of resources (both time and equipment).…”
Section: Perspectivesmentioning
confidence: 99%
“…These include a lack of awareness about the clinical value of HBPM, insufficient knowledge about HBPM best practices, and a lack of resources (both time and equipment). 97 Nevertheless, a substantial body of evidence for the prognostic value of home BP measurements highlight the importance of this approach to the management of CV risk factors in patients with hypertension. HBPM can play a key role in anticipation medicine strategies designed to identify increasing risk and predict the onset of CV events based on a series of data collected over time, allowing proactive interventions to reduce risk and eliminate events.…”
Section: Perspectivesmentioning
confidence: 99%
“…The use of out-of-office BP measurements, using ambulatory BP measurements (ABPM preferred) or home BP measurement (HBPM) to confirm the diagnosis of hypertension, was actually first recom- in Asia in the interim. [33][34][35][36] Although the United States lowered their diagnostic office BP threshold to ≥130/80 mmHg, their diagnostic for both home BP and day ABPM threshold is also ≥130/80 mmHg, and this is puzzling as it has been shown that home BP tend to be around 5 mmHg lower than office readings. However, the United States did lower their ABPM threshold for the 24 h and night by 5 mmHg.…”
Section: Us E Of Out-of-offi Ce B P Me a Surementsmentioning
confidence: 99%